2022
DOI: 10.3390/ijerph19074327
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Sustainability Assessment of the European Union’s Capital Cities

Abstract: The growing flow of people into cities causes several challenges for their functioning. This brings the need to ensure, for example, efficient transport, sustainable waste, and appropriate energy policy. Particularly capital cities are exposed to the above-mentioned risks, due to their large numbers and densities of inhabitants. Therefore, the state of the environment in cities should be monitored systematically. The research aim of this article is to evaluate the level of environmental sustainability in capit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…On another level, population growth negatively impacts the urban ecosystem, not only in the water sector but also in waste, energy, and public transport [21]. Hence, the topic of the circular economy is one of the most recent trends in the literature related to sustainability and is presented as a long-term solution to the waste management issues that have the potential to impact citizens' well-being [22,23].…”
Section: Literature Reviewmentioning
confidence: 99%
“…On another level, population growth negatively impacts the urban ecosystem, not only in the water sector but also in waste, energy, and public transport [21]. Hence, the topic of the circular economy is one of the most recent trends in the literature related to sustainability and is presented as a long-term solution to the waste management issues that have the potential to impact citizens' well-being [22,23].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Однако, по мнению других авторов, методы моделирования, в сравнении со статистическими методами, недостаточно практичны -трудоемки, требуют компьютерной поддержки, недостаточно масштабируемы, трудно интерпретируются результаты [24]. Альтернативой расчету интегрального показатели устойчивого развития может служить однокомпонентная модель, предполагающая оценку только экологической устойчивости [25]. Евростат использует свою специальную методологию оценок достижения ЦУР и ежегодно публикует «Отчет о мониторинге устойчивого развития в Европейском союзе» [26].…”
Section: № 1 (41)unclassified
“…Western European countries have shown increasing interest in and commitment to sustainability and sustainable development. Czupich et al (2022) indicated that European Union (EU) countries have committed to reducing greenhouse gas emissions and fossil fuel consumption. In addition, they have more interest in quality of life and higher environmental rankings than cities on other continents.…”
Section: Introductionmentioning
confidence: 99%